Discovering the Self in Islam: Self-Striving, Self-Regard, and Self-Neglect - Tekke, Mustafa (Universitas Ahmad Dahlan)
AbstractThis study explored some self domains and reviewed them through Islamic perspective, more particularly self-knowledge and faith. It provided an extensive literature on particular concepts of self-striving, self-regard, and self-neglect. To briefly point out, the self has many origins, however deeply noted as such heart, spirit, and psyche in Islam. From these, this study looked at the two known self domains: self-striving, and self-regard. Apart from these concepts, researchers differently chose self-neglect. With this, the study indicated the self-neglect is an important concept as defensive behavior and these all self concepts might be useful as a central of human nature for future experimental development.Keywords: self, Islam, self-striving, self-regard, self-neglect, personality